62.3k views
2 votes
3) 6x - 2w + 9 - 8
use x = 2 and w = 5

User Bpavlov
by
4.8k points

2 Answers

1 vote

Answer:

3

Explanation:

6x - 2w + 9 - 8

x = 2 , w = 5

6(2) - 2(5) + 9 - 8

12 - 10 + 9 - 8

2 + 1

3

Hope this helps .-.

User Nanda
by
5.0k points
4 votes

Answer:

3

Explanation:

6x - 2w + 9 - 8 = 6x - 2w +1

= 6*2 - 2*5 + 1

= 12 - 10 +1

= 2 + 1 =3

User Willy Lazuardi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.